THE SEAWATER AND FRESHWATER INFLUENCE ON EXPANSIVITY BEHAVIORS OF CLAY MINERALS - Dian Agus Widiarso (Marine Geological Institute of Indonesia, 2021)
Semarang City is characterized by an intercalating of loam-silt and clayey units. The behavior of the clay materials in terms of its expansivity changes in the volumetric parameter when it contacts the water. Some problems in the presence of tidal flooding appears when the seawater ingress to the shoreland that causes severe damage to infrastructures. This research attempts to reveal the influence of both seawater and freshwater on the expansivity behaviors of the clayey materials based on its mineral composition. Some tests are performed to observe the volumetric changes in the clay samples after being soaked in seawater and freshwater for twenty-four hours. The X-Ray Diffraction (XRD) tests are conducted on some selected samples by using the bulk method to determine the mineral composition of the samples. The ANOVA test is also introduced in the analysis to distinguish whether the certain mineral types and its composition influencing the clay expansivity behaviors at a confidence level of about ninety-five percent and alpha (α) of about five percent. The result of this research has proven that the presence of montmorilonite minerals is the most influencing factor on the clayey expansivity behaviors when immersed in seawater and freshwater than kaolinite and illite minerals.